PENGARUH LIKUIDITAS, LEVERAGE, UKURAN PERUSAHAAN DAN ARUS KAS OPERASI TERHADAP PROFITABILITAS (Studi Kasus pada Perusahaan Sektor Customer Cylicals yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2024) - Omar Rasyid Abdalla; Dul Muid (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the effect of Liquidity, Leverage, Company Size, and Operating Cash Flow on Profitability in Costumer Cyclicals Companies on the Indonesia Stock Exchange 2021-2024. The population in this study are all Costumer Cyclicals Companies on the Indonesia Stock Exchange 2021-2024 that have complete financial reports. While the sample in this study is Costumer Cyclicals companies that have published financial reports for three years, namely 2021 to 2024. The analysis techniques used in this study are: 1) Descriptive Statistical Test, 2) Classical Assumption Test consisting of Normality Test, Multicollinearity Test, Heterostosity Test, and Autocorrelation Test 4) Multiple Linear Regression, 5) Hypothesis Test consisting of T Statistical Test, F Test, and Coefficient of Determination. The results of this study indicate that Liquidity has a positive effect on Profitability, Leverage has a positive effect on Profitability, Company Size has a positive effect on Profitability and Operating Cash Flow has a positive effect on Profitability.